Research progress, trends, and updates on pollutants removal by Bi2WO6-based photocatalysts under visible light irradiation - Sen Li; Yiling Liu; Yanbo Xiao; Haiyan Ma; Jing Duan (Heliyon, 2024)
In recent years, extensive research has been conducted on bismuth tungstate (Bi2WO6) in the field of photocatalysis owing to its unique crystal structure and favorable bandgap. This study offers a comprehensive review of the research on Bi2WO6-based photocatalysts from 2007 to 2022 using bibliometric analysis. The analysis utilized the Web of Science Core Collection Database and encompassed a dataset of 2064 publications. The bibliometric analysis and science mapping were carried out using the bibliometix R-package and CiteSpace software. This analysis examined and discussed the network of relationships among countries, journals, organizations, authors, and keywords pertaining to the topic and subtopics under investigation. The findings demonstrate that China has played a significant role in this research area and has formed close collaborations with other countries. The identification of highly-cited emerging terms suggests that enhancing the photocatalytic performance of Bi2WO6-based nanomaterials is a primary research focus. Moreover, there has been increasing interest in exploring the synergistic effects of photocatalysis and adsorption as a means to improve catalytic efficiency. This study provides valuable insights for researchers seeking a deeper understanding of Bi2WO6-based photocatalysts.